Field evaluation of combination fungicides against late blight disease in potato (Solanum tuberosum) - SINGH, S S; MER, RAKESH; RENU (The Indian Journal of Agricultural Sciences, 2023)
Potato is commercially important vegetable crop in hills of Uttarakhand and grown as an off season. Farmer’s get remunerative return of their potato because of the off season. It was observed that incidence of late blight disease hampered the production and majority of the farmers used mancozeb fungicide which did not provide expected relief from the menace of late blight disease. Accordingly, interventions were made on combination of fungicides to find out their field efficacy against late blight disease of potato on farmer’s field. The result of the experimentation revealed that two spraying of azoxystrobin + tebuconazole @1 ml/litre of water at moderate severity stage of late blight disease proved to be most effective treatment on reduction of incidence, increase in yield and net income over all other treatments in all the three consecutive years. The T3 has been investigated as best treatment in all the respects among various treatments. The summary of the investigation advocates that two spraying of modern combination of fungicides namely, azoxystrobin + tebuconazole even at moderate severity stage of late blight disease gave tremendous impact on its management throughout the crop season. Considering its impact of three years investigation against late blight disease in off season potato, this novel combination of fungicide may be recommended to the farmer’s of the country.